Pencapaian SIG: SERG / Mohd Bukhari Md Yunus and Abdul Halim Abdul Hamid - Md Yunus, Mohd Bukhari; Abdul Hamid, Abdul Halim (Jabatan Sains Gunaan, 2022)
UiTMCPP-SPECIAL INTEREST GROUP (SIG), background of member (Table)